Affective responses in mountain hiking-A randomized crossover trial focusing on differences between indoor and outdoor activity. - Martin Niedermeier (PLoS ONE, 2017)
INTRODUCTION:Affective responses during physical activity (PA) are important for engagement in PA programs and for adherence to a physically active lifestyle. Little is known about the affective responses to PA bouts lasting longer than 45 minutes. Therefore, the aims of the present study were to analyse acute effects on affective responses of a three-hour outdoor PA intervention (mountain hiking) compared to a sedentary control situation and to an indoor treadmill condition. METHODS:Using a randomized crossover design, 42 healthy participants were randomly exposed to three different conditions: outdoor mountain hiking, indoor treadmill walking, and sedentary control situation (approximately three hours each). Measures included the Feeling Scale, Felt Arousal Scale and a Mood Survey Scale. Repeated measures ANOVAs were used to analyse differences between the conditions. RESULTS:Compared to the control situation, the participants showed a significant increase in affective valence (d = 1.21, p < .001), activation (d = 0.81, p = .004), elation (d = 1.07, p < .001), and calmness (d = 0.84, p = .004), and a significant decrease in fatigue (d = -1.19, p < .001) and anxiety (d = -.79, p < .001) after mountain hiking. Outdoor mountain hiking showed significantly greater positive effects on affective valence, activation, and fatigue compared to indoor treadmill walking. DISCUSSION:The results indicate that a three-hour PA intervention (mountain hiking) elicits higher positive and lower negative affective responses compared to a sedentary control situation and to an indoor PA condition. Outdoor mountain hiking can be recommended by health professionals as a form of PA with the potential to positively influence affective responses. TRIAL REGISTRATION:ClinicalTrials.gov NCT02853760. https://clinicaltrials.gov/. Date of registration: 08/02/2016 (retrospectively registered). Date of enrolment of the first participant to the trial: 05/01/2014.